THE LEADERSHIP ROLE OF THE SCHOOL PRINCIPAL IN IMPROVING MANAGEMENT INNOVATION LEARNING - Badrudin, Badrudin; Ummah, Muftiyyatul; Ropik, Ikbal (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
In facing the complex challenges faced by the education system Nowadays, effective leadership is the key to achieving goals increasing management innovation in learning, collection methods The data needed in writing this article was obtained by Library study technique (library research) is pure library research, that the principal's leadership has a very complex role and strategic in creating a quality learning environment and innovative